STANDARISASI PARAMETER NON SPESIFIK DAN PERBANDINGAN KADAR KURKUMIN EKSTRAK ETANOL DAN EKSTRAK TERPURIFIKASI RIMPANG KUNYIT - Azizah, Barokati; Salamah, Nina (Pharmaciana, 2013)
Turmeric (Curcuma domestica Val.) is one of the plants that contain curcumincompounds with various activity. Use of curcumin from turmeric is widely used in theform of ethanolic extract, but there are ballast substances that cause low levels ofcurcumin. This can be pursued with the manufacture of a purified of ethanolic extract.Ethanolic extract of turmeric was made by maceration using ethanolic 96%. Ethanolicextract soaked with hexane until the hexane phase is clear and purified extract obtainedis insoluble hexane phase. Curcumin levels determined using Thin LayerChromatography (TLC) method with the stationary phase silica gel 60 F and mobilephase of chloroform: ethanolic: glacial acetic acid (94: 5:1) and be analyzedquantitatively using densitometry with a maximum wavelength of 426 nm . The watercontent of the extract determined using toluene distillation method, ash and acidinsoluble ash content determined using gravimetric method. The statistic analysis withLSD showed significant differences of curcumin content and analysis of non-specificparameter values on ethanolic extract and purified extract.